Sustainability of Small-Scale Capture Fisheries Based on Coastal Vulnerability in Pangpang Bay, Banyuwangi Regency, Indonesia - Setyaningrum, Ervina Wahyu; Sambah, Abu Bakar; Wiadnya , Dewa Gede Raka (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research Climate change impacts on coastal vulnerability. Low coastal vulnerability in Pangpang Bay, Banyuwangi Regency. Sustainability of small-scale capture fisheries based on vulnerability. Sustainable small-scale fisheries management. Abstract Teluk Pangpang is one of the water areas that has considerable potential for capturing fisheriesin Banyuwangi Regency, Indonesia. On the other hand, climate change impacts the vulnerability of coastal areas and coastal communities, especially small-scale fishers. This study aims to analyse the coastal vulnerability of Pangpang Bay and formulate a sustainable development plan for small-scale capture fisheries in Pangpang Bay. The research method used a descriptive method with a quantitative approach. Data collection techniques used geographic information systems and focus group discussions (FGDs). The data analysis used was Coastal Vulnerability Index (CVI) analysis with a spatial approach and Participatory Prospective Analysis (PPA). From the CVI analysis, through the assessment of geomorphological parameters, erosion/accretion, coastal slope, distance of plants from the beach, wave height, and average tide range, the level of coastal vulnerability of Teluk Pangpang is included in the low category. Meanwhile, the PPA analysis resulted in seven variables that most influence the sustainability of small-scale capture fisheries, namely climate change, coastal vulnerability, coral reef area and density, number of small-scale fishers, catches, human resources of small-scale fishers, and management of small-scale fisheries resources. Furthermore, the formulation of the sustainability scenario of smallscale capture fisheries in Pangpang Bay is to minimise the impact of climate change and conduct disaster mitigation, improve the human resources of smallscale fishers, and equalise perceptions as outlined in the commitment between all interested parties and small-scale fishing communities.